2020
DOI: 10.1080/1828051x.2020.1826364
|View full text |Cite
|
Sign up to set email alerts
|

Effect of diet supplemented with enzymatically treated Artemisia annua L. on intestinal digestive function and immunity in weaned pigs

Abstract: The present experiment was conducted to evaluate the effect of enzymatically treated Artemisia annua L. (EA) on intestinal digestive function and immune capacity in weaned pigs. Firstly, a total of 300 21-day-old piglets were randomly allotted to five groups, including CON, EA1, EA2, EA3, and EA4 groups (basal diet supplemented with 0, 0.5, 1, 2, 4 g/kg EA, respectively). At 50 days of age, the results showed that pigs in the EA3 group presented significant improvements (p < .05) of growth performance and heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 39 publications
1
11
0
Order By: Relevance
“…In the present study, the content of intestinal pro-inflammatory cytokines, including IL-1β and IL-6, decreased in a dose-dependent fashion with the increase of dietary AAE, suggesting a greater improvement on the anti-inflammatory level of the intestine in broilers. Similar results were observed by Niu et al (25) who found that diet supplemented with enzymatically treated A. annua markedly decreased the content of IL-1β and IL-6 in intestinal mucosa of weaned pigs. Furthermore, studies found that the concentration of pro-inflammatory cytokines IL-1β and IL-6 was reduced, which was related to the content of immunoglobulin in the intestinal mucosa, and increased immunoglobulin in the small intestine promoted efficient prevention of intestinal inflammatory conditions (34).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In the present study, the content of intestinal pro-inflammatory cytokines, including IL-1β and IL-6, decreased in a dose-dependent fashion with the increase of dietary AAE, suggesting a greater improvement on the anti-inflammatory level of the intestine in broilers. Similar results were observed by Niu et al (25) who found that diet supplemented with enzymatically treated A. annua markedly decreased the content of IL-1β and IL-6 in intestinal mucosa of weaned pigs. Furthermore, studies found that the concentration of pro-inflammatory cytokines IL-1β and IL-6 was reduced, which was related to the content of immunoglobulin in the intestinal mucosa, and increased immunoglobulin in the small intestine promoted efficient prevention of intestinal inflammatory conditions (34).…”
Section: Discussionsupporting
confidence: 90%
“…Our study found that the content of secretory IgA (sIgA), IgG, IgM in the small intestine of broilers increased with the increase of dietary AAE. Similarly, Niu et al (25) reported that a diet supplemented with enzymatically treated A. annua increased the content of sIgA and IgG in the jejunum and ileum mucosa of weaned pigs. In poultry, three classes of immunoglobulins bind antigens specifically and remove them through precipitation and phagocytosis.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…13 Moreover, earlier work on weaned piglets showed that A. annua, as a feed supplement, could decrease the concentrations of interleukin (IL)-1β, IL-6, and tumor necrosis factor (TNF)-α in the jejunum. 14 Recently, compelling evidence indicated that maternal A. annua intake is beneficial for their offspring. For instance, dietary supplementation of the enzymatically treated AAE at 1.0 g kg −1 greatly alleviated the oxidative stress in sows, and improved the activity of T-SOD and total antioxidant capacity (T-AOC) in piglet serum.…”
Section: Introductionmentioning
confidence: 99%
“…13 Moreover, earlier work on weaned piglets showed that A. annua , as a feed supplement, could decrease the concentrations of interleukin (IL)-1β, IL-6, and tumor necrosis factor (TNF)-α in the jejunum. 14…”
Section: Introductionmentioning
confidence: 99%